Family relationships, filial piety, and perceived social support on marriage intention among young adults in Malaysia - Chong, Keat Yi; Lim, Xin Yee; Tay, Michi Ting Yin (2025)
The decline in marriage intentions is a global trend, including in Malaysia. Yet, research on Malaysian young adults remains limited. This study investigated the relationships between family relationships, filial piety, perceived social support, and marriage intention among young adults in Malaysia and examined their unique predictive role. A quantitative cross- sectional study was conducted online, with both purposive and convenience sampling methods to recruit Malaysian young adults aged 18 to 26 who are single or in a relationship. The instruments used in this study were the Brief Family Relationship Scale (BFRS), Filial Behaviour Scale (FBS), Multidimensional Perceived Social Support Scale (MSPSS), and Intent to Marry Scale (IMS). A total of 386 participants were recruited (M = 22.41 years; SD = 1.77 years), with 75.3% being female, 85.2% Chinese, and 77% undergraduate students. Pearson correlation indicated a significant positive relationship between filial piety, perceived social support, family relationships, and marriage intention among young adults in Malaysia. Multiple linear regression analysis revealed that perceived social support and filial piety are significant predictors of marriage intention, whereas family relationships are not. Hence, the current findings provide an interesting perspective on marriage intentions and provide empirical evidence for policymakers to develop evidence-based initiatives aimed at increasing marriage intentions among young adults in Malaysia.